2020
DOI: 10.1098/rspb.2020.1860
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility of nutritional strategies within a mutualism: food availability affects algal symbiont productivity in two congeneric sea anemone species

Abstract: Mutualistic symbioses are common, especially in nutrient-poor environments where an association between hosts and symbionts can allow the symbiotic partners to persist and collectively out-compete non-symbiotic species. Usually these mutualisms are built on an intimate transfer of energy and nutrients (e.g. carbon and nitrogen) between host and symbiont. However, resource availability is not consistent, and the benefit of the symbiotic association can depend on the availability of resources to mutualists. We m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 62 publications
0
11
0
1
Order By: Relevance
“…In other words, the external environment can influence the expression of specific genes leading to differences in metabolic and biosynthetic processes in giant sea anemones tentacles. For instance, symbiont activity in Anthopleura is susceptible to external food availability, shifting the balance between heterotrophic and autotrophic lifestyles (44). Sea anemones absorb more ammonia during the daytime than at night, indicating that ammonia uptake is driven by the photosynthetic activity of Symbiodiniaceae (45).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the external environment can influence the expression of specific genes leading to differences in metabolic and biosynthetic processes in giant sea anemones tentacles. For instance, symbiont activity in Anthopleura is susceptible to external food availability, shifting the balance between heterotrophic and autotrophic lifestyles (44). Sea anemones absorb more ammonia during the daytime than at night, indicating that ammonia uptake is driven by the photosynthetic activity of Symbiodiniaceae (45).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, adaptive benefits could falsely appear to arise from host populations if studies fail to take the genetic variation of the symbionts into account. Future work should experimentally test whether these genetic patterns actually reflect the enhanced performance of the symbiont (and possibly the holobiont) in its local environmental conditions, given that some symbiont strains could be parasitic in some environmental contexts [ 52 ], and that the partnership responds to fluctuations in the host nutritional budget differently, depending on the host species [ 54 ]. Fully characterizing the costs and benefits of the partnership across multiple scales is a crucial next step which can be used to test hypotheses that explain how or if the relationship remains stable over time, to reveal the genetic basis of locally adapted traits, and to predict how host and symbiont populations will respond (independently and as partners) as the climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the effects of horizontal and vertical animal migration (e.g. sea turtles, fish, zooplankton), or seabird excretion on the overall food web could be locally significant in shallow or even mesophotic waters depending on the topography, but are still largely overlooked (Yahel, Yahel & Genin, 2005;Becker, Brainard & Van Houtan, 2019;Thibault et al, 2022).…”
Section: Heterotrophy In Mafs Among Different Environmental Condition...mentioning
confidence: 99%
“…In mixotrophic organisms, numerous studies have shown that heterotrophy is an important source of nitrogen and phosphorus (Ribes et al ., 1998, 2003), and improves the physiological performance of these organisms under different environmental conditions (e.g. Klumpp, Bayne & Hawkins, 1992; Rodrigues & Grottoli, 2006; Towle, Enochs & Langdon, 2015; Bedgood, Mastroni & Bracken, 2020), especially when symbiotic associations are facultative (Aichelman et al ., 2016). In particular, sustained reliance on heterotrophic diets may represent an adaptive strategy to climatic stressors (Hughes & Grottoli, 2013; Meunier et al ., 2022), alongside other strategies such as farming and feeding on their autotrophic symbionts (Wiedenmann et al ., 2023).…”
Section: Heterotrophy In Mafs Among Different Environmental Condition...mentioning
confidence: 99%